Reproductive Biology of Mystus nigriceps C.V, 1840 from the Tapung Kiri River, Pantai Cermin Village, Tapung District, Kampar Regency, Riau Province - Wiwit Kartika Sari; Ridwan Manda Putra; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Mystus nigriceps is present in the Tapung Kiri River. A study aims to understand the reproductive biologi of M. nigriceps has been conducted from April to May 2018. Fish sampling were conducted once/ week. Parameters measured were sex ratio, gonad maturnity level, gonad somatic index (GSI), fecundity and egg diameter. Results shown that there were 37 males and 63 females (sex ratio 1:2). There were 2 differences between male and female fish. There was a white spot in the male fish tail, and the shape of the male genital papilla is pointed, while that of the female is blunt. The size of females ranged from 86-157 mm (SL) and body weight was 7.28 to 93.23 g, while that of the males was 86-154 mm (SL) and the body weight 31.59 to 29.90 g. The GSI of females ranged from 0.12 to 17.43%, while that of males was 0.09 to 2.91%. The fecundity was 9.907 to 18.948 egg/ fish and egg diameter was 0.54 to 0.58 mm.Keyword: Sex Ratio, Gonad Maturity Level, Gonad Somatic Index, Fecundity